If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x = 12y + 72 Reorder the terms: -6x = 72 + 12y Solving -6x = 72 + 12y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = -12 + -2y Simplifying x = -12 + -2y
| 18-b=15 | | 7(4+2a)=84 | | -4+9x=-30 | | 78x+27=3 | | 9m-4(2m-2)=14 | | 6x-7=2x-2 | | 9x-18=-36 | | 9x+1=9x-7 | | (80-x)3x=180 | | 4x-1=8-2x | | 8+3q=11+2q | | -13=6-7 | | 2x-2=6x-4 | | 2x-4(x-3)=-9+5x-14 | | 3b+12-5b=22 | | 0.07-0.06(5x+4)=0.06x+0.13 | | 4x+13=-7x-30 | | 4x^2-26-14= | | 32m+54m+22=0 | | 6x-4x+20=-16 | | 2+3v=-6v-16 | | 3x+20+2(4x+4)=2x | | 26-(4x-11)=5(x+7) | | -(5z+1)=18 | | 4x+8-3x=14 | | 6x^3=5x^2 | | 3x+5.2=2-5y | | x+5=x+0 | | -13+7=-h-7+7 | | 3x-15=17-x | | 3(5y+2)-y=(2y-3) | | x=23-(-11) |